TURN TAKING STRATEGIES IN POLITICAL DEBATES - Desi Dwi Natalia; Fajar Subekti; Ni Ketut Mirahayuni (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2019)
This article reports on two separate studies—Natalia (2019) and Subekti (2019)—on communication mechanism in political debates. Specifically these studies focus on turn taking strategies adopted in political debates by political figures during their campaign for presidency or in dealing with specific issues. Both studies adopted Stenstrom’s (1994) classification of turn taking strategies which include three main strategies: taking the turn, holding the turn, and yielding the turn, each of which was further specified into more specific strategies. The data were two Youtube videos: first, Trump and Clinton First Presidential Debate 2016 (36 minutes 22 seconds [Natalia, 2019]) and second, BBC World Debate “Why Poverty”November 30,2012 (47 minutes 16 seconds, [Subekti, 2019]). Employing descriptive qualitative, with the aim of analyzing turn taking strategies adopted in the debates, both studies found interesting points: first, Stenstrom’s three strategies appeared in the debates; second, taking the turn strategy was the dominant strategy, followed by holding the turn strategy and the least used one was yielding to turn; and third, interruption which was a specific type of taking the turn strategy seems to be most often used in the debater’s attempt to maintain the turn and present their points and thus dominate the debate.